Impact of physical activity on executive functions: a moderated mediation model - Zhao, Guoguo; Sun, Kaihong; Fu, Jian; Li, Zhe; Liu, Dongbin; Tian, Xin; Yang, Jiehui; Zhang, Qiushi (Frontiers in Psychology, 2024)
Objective: To provide both empirical support and a theoretical framework for systematically improving and optimizing the cognitive capabilities of college students through physical activity, while considering the mediating and regulating impacts of self-efficacy and negative emotion.Methods: The study employed an overall random sampling method, examining 500 college students from five universities in Jiangsu Province using the Physical Activity Rating Scale (PARS-3), Adult Executive Function Scale (ADEXI), Positive and Negative Emotion Scale (PANAS), and General Self-Efficacy Scale (GSES).The findings indicated that the average age of the participants was 18.41± 0.73years, encompassing 215 male students (43%), and 185 female students (57%). Engagement in physical activity was significantly and positively correlated with executive function (β = 0.246, p < 0.01), inversely associated with negative emotion (β = -0.137, p < 0.01), and demonstrated a significant positive predictive impact on self-efficacy (β = 0.183, p < 0.01). Self-efficacy was observed to partially mediate the relationship between executive function and physical activity.In addition, negative mood was identified as playing a partial mediating and modifying role in the relationship between executive function and physical activity.Conclusion: Increasing college students' daily physical activity participation not only benefits their executive function, self-efficacy, and confidence levels but also exerts a limited positive impact on negative mood, with the potential to regulate the intensity of negative emotion.